Behavior of arch composite beam: Experimental and numerical investigation - Abdelrahim Sabsabi; Oussama Baalbaki; Adnan Masri; Hassan Ghanem (Results in Engineering)
The behavior of arch composite beams prestressed with external tendons is experimentally and numerically investigated in this study, combining the structural efficiency of arch geometry, composite action, and external prestressing. Unlike traditional studies focused on straight beams, this research explores curved composite systems, offering a more efficient alternative for infrastructure applications. Three full-scale beams were tested: a fully prestressed composite beam, a fully composite beam without prestressing, and a partially composite beam with reduced shear connectors. Load–deflection behavior, failure modes, tendon stress development, and strain distributions were analyzed. A finite element model using ABAQUS was developed and validated against experimental results, and a parametric study was performed to assess the influence of initial prestress levels. Results demonstrated that external prestressing increased the ultimate moment capacity by 80 %, reduced mid-span deflection by 60 %, and significantly redistributed internal stresses, promoting a favorable arching effect. Furthermore, reducing the number of shear connectors by 50 % led to a 28 % reduction in stiffness and a 20 % increase in ductility, with negligible impact on ultimate load. These findings highlight the potential of externally prestressed curved composite beams as a structurally and economically optimized solution for bridge and infrastructure systems.